2013
DOI: 10.1097/aog.0b013e318293698c
|View full text |Cite
|
Sign up to set email alerts
|

Early Oral Intake and Gastrointestinal Function After Cesarean Delivery

Abstract: Early oral intake after cesarean delivery improves the return of gastrointestinal function and does not increase the occurrence of gastrointestinal complications. A clinical implication based on the findings of the current evidence is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 22 publications
5
15
2
1
Order By: Relevance
“…Second, EOF could be beneficial for these patients: it contributed to a faster return of gastrointestinal tract function, reduced the amount of care needed postoperatively, and decreased time to first breastfeeding. The results for postoperative complications are in accordance with the findings of a previous meta‐analysis [10]. However, only randomized controlled studies were included in the present analyses—including six that were not analyzed in the previous meta‐analysis—which increases reliability [31].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Second, EOF could be beneficial for these patients: it contributed to a faster return of gastrointestinal tract function, reduced the amount of care needed postoperatively, and decreased time to first breastfeeding. The results for postoperative complications are in accordance with the findings of a previous meta‐analysis [10]. However, only randomized controlled studies were included in the present analyses—including six that were not analyzed in the previous meta‐analysis—which increases reliability [31].…”
Section: Discussionsupporting
confidence: 86%
“…However, this approach has been challenged. A series of clinical trials [5–8] and two systematic reviews [9,10] indicated that early intake of fluid or food after cesarean delivery is safe and beneficial. The advantages of such early intake include rapid return to normal bowel function, early ambulation and discharge, reduced analgesic requirements, and decreased risk of sepsis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Early oral feeding has been associated with a faster recovery of intestinal function (i.e. resolution of ileus) , reduced morbidity (e.g. less infectious complications and improved wound healing and immunity) and improved quality of life (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent meta-analysis, early oral intake after cesarean delivery was associated with the earlier return of gastrointestinal function and did not increase the occurrence of gastrointestinal complications. 18 Though not all studies included in this meta-analysis reported LOS, one randomized controlled trial found early feeding to be associated with a significantly shorter hospital stay (4.8 vs. 6.7 days). 19 …”
Section: Discussionmentioning
confidence: 89%